ANALISIS PENGARUH FAKTOR EKONOMI MAKRO TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG GO PUBLIC DI BURSA EFEK INDONESIA - Musthafa Musthafa (EKUITAS (Jurnal Ekonomi dan Keuangan), 2009)
Stock investment is different from saving investment, deposits or foreign exchange, because stock investment always encounters many investors with their various profit expectations. Each stock investor has always to monitor the latest stock assurance development and observe the stock flow in the stock markets carefully and thoroughly, because they influence the stock prices.Many factors influence the stock prices, including the seller or buyer psychological factor, company condition, interest rate, rupiah exchange rate against foreign currency, economic condition, government policies, inflation rate, the country’s political and safety condition, and many others. This study analyzes the influence of those factors on the stock prices and is entitled “An Analysis of the influence of Macroeconomic Factors on Stock Prices in Go Public Manufacture Companies in Indonesia Stock Exchange “.The population are 151 manufacturing companies, 116 of which were analyzed in 3 years (2005 – 2007). The result shows that macroeconomic (inflation, SBI rates and rate of exchange) variables have  significantly influenced the stock prices.